A comparative study between E.Coli O157:H7 and Coliform bacteria isolated from locally soft cheese - Al-Jaleel, Raghad A. Abd (The Iraqi Journal of Veterinary Medicine, 2008)
The main objective of this study was to isolate, identify andenumerate the E.coli O157:H7 bacteria and coliform bacteria fromlocally manufactured soft cheese.A total of 50samples of local soft cheese were collected and examinedfrom local markets of (5) different areas of Baghdad city which was Aldora,Al-Amria,Al-Kadmia,Al-Karada,Al-Kazalia 10 samples for eacharea.The results showed that the highest average counts of E.coli O157:H7and coliform bacteria was in Al-Dora 73.63 × 105and 956 × 105cfu/mlwhile the lowest average counts in Al-Kazalia 3.12× 105and 43.7×105cfu/ml .The result of the statistical analysis showed that there were a significantdifferences (p<0.05) between E.coli O157:H7 and coliform bacteriabetween Al-Dora and the other areas in this study which was Al-Kadmmea,Al-Karada,Al-Ammrea,Al-Kazalia but there were nosignificant differences (p<0.05) between the tow kinds of bacteria ineach area.It was conducted that the higher average of pollution for locally softcheese with E.coli O157:H7 was in Al-Dora , the reason of this higherpollution may be due to un healthy condition during milk collection usedfor milk processing or during the processing itself